PENINGKATAN KECERDASAN EMOSIONAL DAN SPIRITUAL MELALUI INTENSITAS PUASA SENIN KAMIS - Rokim Rokim (Universitas Islam Lamongan, 2017)
As human beings God have given them the potential of emotion to do bad or good things. Totally eliminating emotion is also not good. Whereas on account of the emotion ones are eager to eat when they are hungry, they are sad, happy, have a sense of love and so on. So the most important thing is controlling and directing the emotion so that it becomes a guide toward good things.Fasting on Mondays and Thursdays as part of refraining from any action contrary to the religious teachings will bring self-control, honesty, social awareness, the meaningfulness of life not do things that deviate from the teachings of Islam. Fasting could have a positive impact on a person's religiosity, but not all fasting could increase spiritual intelligence. Only fasting that is done with pure heart and soul will foster spiritual intelligence. Fasting that is done by involving conscience is the true one for being able to become an important instrument to purify the heart and soul. Fasting on Mondays and Thursdays will be able to improve the emotional and spiritual intelligence.Keywords: Intelligence, emotional and Spiritual